Draft Second Five Year Plan Jammu and Kashmir - Planning Commission (Planning Commission, 1955)
It was divided into two sectors named. As the Central. Sector and the State Sector in the Central Sector schemes productive of financial returns which are charged to capital were, in the main, included In the State sector all development expenditure on Education, Health, Cottage and. Small Scale Industries, Tourism and rural and Urban Water Supply were included Besides these some provision was also Scale for Road Development, power and Irrigation schemes but that was an insignificant proportion of the torsi expenditure in the Central Sector and also of the total expenditure on these items in the Central sector According to this distribution the total cost of the Plan was 10 chores of rupees distributed as 7 crores for the Central Sector and 7 crores for the State sector.
Government of Jammu and Kashmir
Government of Jammu and Kashmir
Keywords: Labour Welfare; Industrial Development; Road and Transport Development; Information & Publicity; Local Bodies; Backward Area Development; Statistical Schemes; Industrial Research; Development of Fisheries; Jammu and Kashmir State; Road Development